Arnaldo Biscardi and ancient Greek law. Some remarks on the judicial role of the Athenian courts, between gnome dikaiotate and epieikeia: Peer-reviewed article (Italian Review of Legal History, 2023)
In an essay published in 1970, Arnaldo Biscardi deals with a controversial clause in the oath sworn by Athenian popular judges before entering their office: they will decide the case according to the γνώμη δικαιοτάτη, «the best judgement». Biscardi reaches the conclusion that γνώμη δικαιοτάτη is not a means to bypass the law in the name of equity, as argued by some scholars; it is, instead, a guide to the judges, so that they can express their vote according to the authentic meaning of the law and the intent of the lawgiver. The most recent and sound studies on Attic trial confirm that, as Biscardi had already demonstrated, the outcome of a trial in Athenian courts was the result of a strict enforcement of the law and of its most correct interpretation.
Keywords: Rule of Law; Athenian Trial; Athenian Courts; Interpretation of the Law; Greek Law